2011
DOI: 10.1073/pnas.1110629108
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of canonical Wnt signaling by the extracellular matrix component biglycan

Abstract: Although extracellular control of canonical Wnt signaling is crucial for tissue homeostasis, the role of the extracellular microenvironment in modulating this signaling pathway is largely unknown. In the present study, we show that a member of the small leucine-rich proteoglycan family, biglycan, enhances canonical Wnt signaling by mediating Wnt function via its core protein. Immunoprecipitation analysis revealed that biglycan interacts with both the canonical Wnt ligand Wnt3a and the Wnt coreceptor low-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
137
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 37 publications
3
137
0
3
Order By: Relevance
“…Some studies showed that BMP-2 activates Wnt/β-catenin in C2C12, C3H10T1/2, and MC3T3-E1 cells (Rawadi et al, 2003;Zhang et al, 2009), while others reported the lack of such effect (Nakashima et al, 2005). In a recent bone fracture-healing model, the callus of BGN-deficient mice reduced gene expression levels of Wnt-induced secreted protein 1, indicating a role of BGN in Wnt signaling (Berendsen et al, 2011). The discrepancy between the current study and those reports could be due to the assay conditions, such as timing (1-hr incubation in this study), passage effect, and culture conditions, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that BMP-2 activates Wnt/β-catenin in C2C12, C3H10T1/2, and MC3T3-E1 cells (Rawadi et al, 2003;Zhang et al, 2009), while others reported the lack of such effect (Nakashima et al, 2005). In a recent bone fracture-healing model, the callus of BGN-deficient mice reduced gene expression levels of Wnt-induced secreted protein 1, indicating a role of BGN in Wnt signaling (Berendsen et al, 2011). The discrepancy between the current study and those reports could be due to the assay conditions, such as timing (1-hr incubation in this study), passage effect, and culture conditions, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Each binding cycle began with the delivery of recombinant human BGN (24)(25)(26)(27), which had been purifi ed by ion exchange chromatography as described above and kindly provided by Dr. Rick Owens (LifeCell Corporation; Branchburg, NJ). The BGN was added to the sample channel at a concentration of 34 g/ml protein at a fl ow rate of 20 l/min for 180 s followed by a 300 s stabilization period to achieve ‫ف‬ 10% saturation of the mAb sample channel surface (1,239 ± 18 RU, n = 30) (see supplementary Fig.…”
Section: Plasma and Lipoprotein Cholesterolmentioning
confidence: 99%
“…Extracellular matrix (ECM) components, such as biglycan, glypican, and heparan sulfate, are able to modulate the activation or the inhibition of Wnt/b-catenin signaling by binding Wnt to the frizzled receptor and its coreceptor LRP6. 28 It has been reported that biglycan directly interacts with Wnt3a at Cterminus, which enhances b-catenin/T cell factor mediated transcriptional activity. 28 Syndecan-4 was shown to inhibit Wnt/b-catenin signaling through regulation of LRP6 and R-spondin 3.…”
Section: Wnt Interactions With Extracellular Matrix and The Effect Ofmentioning
confidence: 99%
“…28 It has been reported that biglycan directly interacts with Wnt3a at Cterminus, which enhances b-catenin/T cell factor mediated transcriptional activity. 28 Syndecan-4 was shown to inhibit Wnt/b-catenin signaling through regulation of LRP6 and R-spondin 3. 29 The influence of acellular ECMs on b-catenin expression and the response to Wnt activator and inhibitor were demonstrated recently.…”
Section: Wnt Interactions With Extracellular Matrix and The Effect Ofmentioning
confidence: 99%
See 1 more Smart Citation